Pengaruh Penambahan Lumpur Geothermal Dan Serat Baja Ban Bekas Terhadap Beton - Devita Mayasari; Tri Yuhanah; Budi Wicaksono (FORUM MEKANIKA, 2019)
Concrete is a very popular construction material, widely used in construction. The waste that is in the surrounding environment begins to be used for mixed materials in the manufacture of concrete, one of which is geothermal mud (geothermal sludge) which has pozzolanic properties because it contains alumina silica minerals so that it can be used instead of cement. Waste steel fiber tires used residue from vehicles is an added material that can be used to improve the mechanical properties of concrete. This study aims to determine the effect of adding geothermal mud and used steel fiber to concrete. Planned concrete fc '30 MPa with geothermal mud as partial substitution of 20% cement and used tire steel fibers with variations of 0%, 0.5%, 1% and 1.5% of the weight of concrete. Concrete Variation 4 (1.5% used tire steel fiber + 20% geothermal mud) has the highest compressive strength of 32.13 MPa compared to normal concrete of 30.006 MPa. For the splitting tensile strength variation 4 is 1.8 MPa and its flexural strength is 2.457 MPa while the normal concrete is splitting tensile strength of 1.6 MPa and its bending strength is 2.210 MPa.